Black Phosphorus Nanosheets Modified with Au Nanoparticles as High Conductivity and High Activity Electrocatalyst for Oxygen Evolution Reaction. Issue 44 (11th October 2020) - Qiao, Hui; Liu, Huating; Huang, Zongyu; Ma, Qian; Luo, Siwei; Li, Jun; Liu, Yundan; Zhong, Jianxin; Qi, Xiang
Abstract: As a unique monoelemental 2D material, black phosphorus (BP) has attracted great research interest in the field of electrocatalytic oxygen release due to its special electronic structure and satisfactory catalytic activity. However, the limited catalytic activity of BP nanosheets limits its practical application. Here, a one‐pot hot solution method is used to synthesize a mixed‐dimensional hybrid of BP nanosheets loaded with Au nanoparticles (BP/Au). The electrochemical test results show the BP/Au exhibits excellent electrocatalytic oxygen evolution performance with an ultra‐low onset potential (1.36 V) and Tafel slope (68.1 mV dec −1 ). The first‐principles calculation results further support the experimental results, in which the loading of Au nanoparticles realizes the transition of BP from the semiconductor phase to the metal phase, which makes the BP/Au exhibit faster carrier mobility. The BP/Au also exhibits a Gibbs free energy closer to the optimal value of the OER. This is because Au nanoparticles can inject free electrons unto the surface of BP and realize the coupling effect between the local semiconductor and metal, thereby effectively improving the carrier mobility and catalytic activity. This work fully confirms that the BP/Au is a suitable candidate for electrocatalytic oxygen evolution, and provides effective strategies for constructing efficient electrocatalysts. Abstract : A simple one‐pot hot solution method is used to synthesize a mixed‐dimensional hybrid of black phosphorus (BP) nanosheets loaded with Au nanoparticles (BP/Au). The loading of Au nanoparticles can effectively improve the conductivity and catalytic activity of BP nanosheets, thereby effectively enhancing its electrocatalytic oxygen generation performance.